Validating a consumer-based service brand equity (CBSBE) model in the airline industry - Sarker, Moniruzzaman; Mohd-Any, A. A.; Yusniza, K. (Elsevier, 2021)
Over time, scholars have argued that consumer-based brand equity (CBBE) models are less suitable for servicedominant brands, mainly because the role of customer experience with services is often disregarded. Also, the absence of two essential components, brand consistency and perceived value, signals a lack of depth in creating service brand equity. To address these gaps, we examine service-branding theory by conceptualizing and validating a consumer-based service brand equity (CBSBE) model in Sarker et al. (2019) in the context of airlines. Airline service direct experience and brand consistency are highly important aspects for strengthening brand equity components of services. Subsequently, maximizing perceived value, followed by creating favorable brand meaning are the nucleus of branding services. Using the most advanced PLS-SEM techniques, our CBSBE model is highly robust in explaining the theoretical notion of creating service brand equity. Thus, achieving a pleasant and desirable experience and maintaining consistency across direct service touchpoints would be an effective strategy for service organizations.